Prerogative of the President in About the State of Emergency (Comparison of Indonesia with the United States) - Farid Wajdi; Andryan Andryan (International Journal Reglement & Society (IJRS), 2021)
In the 1945 Constitution there are two regulations regarding emergency situations (danger) which are regulated in two articles, namely Article 12 and Article 22. Article 12 of the 1945 Constitution states, "The President declares a state of danger, the conditions and consequences of a state of danger are determined by law". Then Article 22 paragraph (1) of the 1945 Constitution states, "In the event of a compelling urgency, the President has the right to stipulate government regulations in lieu of law". From the above provisions, it can be seen that there are two categories of circumstances according to the 1945 Constitution, namely (1) conditions of danger and (2) matters of compelling urgency. The terms (legal terms) used in the two articles are clearly different, the first term uses the term "danger" which is nothing but the same as the definition of an emergency. This research uses normative juridical research. The problem approach used in this research includes a legal approach, a conceptual approach, a case approach and a comparative approach. This research is a deductive research that describes legal events and legal consequences associated with the establishment of state emergencies in several countries. The data obtained were collected and analyzed qualitatively with a descriptive-analytical model. So that the results can be described comprehensively and systematically regarding the basic considerations in establishing the rule of law. The provisions regarding Article 12 and Article 22 paragraph (1) of the 1945 Constitution are basically also related to Article 10 and Article 11 paragraph of the 1945 Constitution. The problem in this research is how to regulate the legal basis for determining the status of a state emergency in Indonesia. with the United States? What is the President's authority in determining the state of emergency status in Indonesia with the United States?